(untitled) (Global Journal of Science Frontier Research, 2012)
Ten millions more are killed and debilitated by a host of mosquito-borne diseases, including filariasis and dengue.One alternative measure of control involves the use of entomopathogen, Bacillus thuringiensis (Bt)-a gram positive spore-forming soil bacteria that produces δ-endotoxins, which make-up the crystalline inclusions as part of its metabolic process. In this study the local isolate of Bt was identified through its morphological and biochemical characteristics and was tested for toxicity against Aedes aegypti and Culex quinquefasciatus larvae. With concentrations 0.5, 1.0, and 3.0% of Btspore-crystal complex, samples were subjected to 24, 48, and 72h of exposure. In both species, the 72 h of exposure showed a mean difference of significance at the 0.05 level. Since the crystal proteins bind specifically to certain receptors in the insect’s intestine, certain processes require a longer span of time to exhibit their effects on the mosquito species. Hence, the activity of Bt with respect to span of incubation had a significant effect on A. aegypti and C. quinquefasciatus larvae. Also, the results differed with respect to the species of tested mosquito.